The impact of omega-3 on recurrent seizures in epileptic patients: A case study with evidence-based approaches - Nadiyah Wijayanthie; Wiji Lestari (Indonesian Nutrition Association, 2024)
Background: Epileptogenesis is also associated with increased production of excessive pro-inflammatory cytokines” which shows connection between pro-inflammatory cytokines as triggering factor with omega-3 which has anti-inflammatory effect. Omega-3, known for its neuroprotective and anticonvulsant properties, exhibits promising effects on epileptic seizure attacks. Objective: This study aimed to evaluate the effect of omega-3 supplementation on the incidence of seizures in epilepsy patients. Methods: This study used a literature search using advanced queries in the databases PubMed, Scopus, ProQuest, and Cochrane Library, and combined MeSH terms with Title/Abstract. The collected literature is discarded if there are duplicates, then literature is filtered that meets the eligibility criteria. We used the Oxford Center for Evidence-Based Medicine as a means of critical appraisal and determining the level of evidence of the selected literature. Results: Four chosen literatures were critically assessed. Two articles indicating no significant difference between omega-3 and placebo and two articles showed had a significantly higher number of seizure-free days than placebo. The first article, involving 78 adults, reported a 50% reduction in seizure risk with a frequency RR of 0.57, 95% CI 0.19 to 1.75 (IS = 0%) indicating no significant difference between omega-3 and placebo groups after 12 weeks of treatment. The second study, comprising mostly non-significant findings, demonstrated no significant correlation between omega-3 and epilepsy attacks in epilepsy patients. The third literature revealed seizure occurrences per month in the EPA group (9.7±1.2), DHA group (11.7±1.5), and placebo group (16.6±1.5). Incidence rate ratio (IRR) adjusted for seizure type in EPA and DHA groups compared to the placebo group were 0.61 (CI = 0.42–0.88, p = 0.008, a 42% reduction) and 0.67 (CI = 0.46–1.0, p = 0.04, a 39% reduction), respectively. Both treatment groups had a significantly higher number of seizure-free days compared to the placebo group (p < 0.05). The fourth study reported intervention group frequency (4.72 ± 1.6, p= 0.014) and placebo frequency (11.64 ± 1.63, p=0.014) with intervention group seizure duration (6.64 ± 1.39, p=0.009) compared to placebo group (14.36 ± 2.18, p=0.009). Conclusion: Omega-3 supplementation may be considered for management in patients with recurrent epileptic seizures, although its effect on reducing seizure frequency remains inconsistent.